ISLAND DEVELOPMENT UNDER PRESSURE: POPULATION GROWTH AND DEMOGRAPHIC CHANGES IN SOUTH ANDAMAN - Bera, Swagata (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study analyzes population growth and demographic changes in South Andaman District from 1991 to 2001, assessing their consequences for developmental pressures on island ecosystems. The Andaman archipelago is a distinctive and ecologically fragile area where understanding population dynamics is essential for sustainable development planning. Utilizing census data from 1991 and 2001, spatial mapping and statistical analysis of essential demographic factors across the selected populated islands of South Andaman District were performed. Five thematic maps were generated for each time period to visualize patterns in population distribution, population density, settlement density, sex ratio, and literacy rates. Results indicate clear spatial patterns, with population density predominantly situated along the eastern coastline regions of South Andaman Island and in junction villages such as Govinda Nagar (Havelock Island) and Neil Kendra (Neil Island). Although the total population density was very low (<500 persons/km²), the villages next to urban areas (Port Blair Municipal Council, Garacharma, and Bambooflat) displayed medium to high density levels. Temporal analysis revealed a trend towards increased density classifications from 1991 to 2001. The district had enhanced sex ratios and literacy rates, with the majority of villages classified as medium to very high for both metrics. Analysis of labor participation indicated that 36.69% of the population was involved in economic activities, with "other workers" and "cultivators" constituting the primary occupational categories, signifying a mixed service-agricultural economy. The findings underscore the developmental challenges confronting South Andaman’s delicate island ecosystem, especially in regions undergoing swift demographic transformations. The geographical concentration of population in particular areas indicates the necessity for focused development policies that reconcile human requirements with ecological sustainability. This research offers essential baseline data for policymakers to develop measures to reduce population-induced pressures on the island’s finite resources.